The Impact of Inventory Strategy on Operations Performance: Study on Bandung City Traditional Market Trader - Muhammad Ainul Fahmi; Ria Arifianti; Raden Marsha Aulia Hakim (West Science Business and Management, 2023)
Traditional markets are trading activities between buyers and sellers as a process of interaction between communities to realize prosperity. However, the development of modern retailers has entered the suburbs since the issuance of the trade deregulation policy in 2008. If there is no systematic effort to understand the characteristics and existence of traditional markets and traders, the livelihoods of around 12.6 million traditional market traders will be threatened. On the other hand, the Covid-19 post-pandemic is a major event for the supply chain in almost any business. Therefore, one way for traders to overcome the impact of the risk of trade deregulation policies and post-pandemic conditions is to create an inventory strategy to improve the performance of their business operations. The results of research using SEM PLS in this study found that Economic Order Quantity (EOQ) and Strategic Supplier Partnership (SSP) did not affect Operations Performance (OP) at traditional market traders in Bandung City while Just-in Time (JIT) significantly and positively increased Operations Performance (OP) of traditional market traders in Bandung City.